Order Reduced Methods for Quad-Curl Equations with Navier Type Boundary Conditions (Journal of Computational Mathematics, 2020)
Quad-curl equations with Navier type boundary conditions are studied in this paper.Stable order reduced formulations equivalent to the model problems are presented, andfinite element discretizations are designed. Optimal convergence rates are proved.